Perancangan Interior Librarica (Cafe & Bar) Di Semarang - Liem Adrian Lukito; laksmi kusuma wardani; lucky basuki (Intra, 2015)
The interior design of Librarica (Cafe & Bar) serves as an interior medium that combines a cafe, lounge, and bar with a library and provides a variety of books. This café & bar with library concept is made as a place to relax and to gather with each other while reading books and eating great foods, which capable of attracting a greater public interest especially from young generation to read books and re-visit the cafe. Considering the huge number of people who come to a cafe to eat, relax, and communicate with their friends, this library cafe would be a very suitable choice for people to try. By facilitating the customer activities in order to give a relaxing and comforting environment to the people, the supporting rooms that will be used by the customer shall be designed or adjusted to the behavior of people around. Therefore, this cafe is able to accommodate the people’s activities which suit their behavior so that the convenience, safety, and the relaxing state can be achieved in this library cafe. So, with the effort of making this representative interior design concept, it is expected that the interest in reading books and the numbers of potential customers of this cafe will increase.